2017
DOI: 10.1097/mop.0000000000000458
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen saturation targeting by pulse oximetry in the extremely low gestational age neonate: a quixotic quest

Abstract: Purpose of review A collaboration of comparative effectiveness research trials of pulse oximeter saturation (SpO2) targeting in extremely low gestational age neonates (ELGANs) have begun to report their aggregate results. We will examine the results of those trials, collectively referred to as the Neonatal Oxygenation Prospective Meta-analysis, or NeOProM. We will also discuss the uncertainties that remain and the clinical challenges that lie ahead. Recent findings The primary outcome from NeOProM was a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
1
11
0
3
Order By: Relevance
“…This is consistent with our findings. Others have suggested that a somewhat lower target could be a better balance of outcome risks 10 14 27 28. Our data would support the latter as well, if the clinical goal was to reduce the likelihood of hyperoxemia and accept a marginal increase in the likelihood of hypoxemia.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This is consistent with our findings. Others have suggested that a somewhat lower target could be a better balance of outcome risks 10 14 27 28. Our data would support the latter as well, if the clinical goal was to reduce the likelihood of hyperoxemia and accept a marginal increase in the likelihood of hypoxemia.…”
Section: Discussionsupporting
confidence: 72%
“…Marked changes in outcome of preterm infants have consistently been reported with shifts in related practice guidelines5–7 and in randomised evaluations 8 9. However, identification of an optimum SpO 2 target range has been elusive 10. More recent analyses have suggested that episodic exposure to SpO 2 extremes is more important than selection of the SpO 2 target range 11–14.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assisting the titration of supplemental oxygen treatment in preterm neonates may also be a particularly useful application. Large prospective trials have shown that higher SpO 2 target ranges (SpO 2 = 91–95%) manifest in increased risk of retinopathy, but that lower SpO 2 targets (SpO 2 = 85–90%) manifest in increased risk of death . However, recognizing that even healthy infants have a substantial incidence of short, shallow desaturations, detailed oximetry quantification may allow ‘normal’ ranges to be defined, and thereby facilitate development of sophisticated oxygen targeting strategies …”
Section: Discussionmentioning
confidence: 99%
“…A oxigenoterapia suplementar é uma das intervenções terapêuticas mais utilizada na Unidade de Terapia Intensiva Neonatal. Desse modo, pode-se afirmar que, da mesma forma que a comida, o calor, e a água, também o oxigênio é vital para manter a vida, no entanto, seu excesso pode causar danos (1) .…”
Section: Introductionunclassified